Manna, Salwa, Semantik Manna dan Salwa: (Analisis Semantik dalam tafsir Al-Qur’an dan Tafsirnya dan Tafsir al-Mishbah) - qonitah hafidzah (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
Manna and Salwa> is a term mentioned simultaneously in the Qur'an three times in three different letters. For the word Manna it self is repeated 37 times with 27 forms in different letters, while for the word Salwa> it self is mentioned 3 times in different letters. Of course, the word has a different meaning in each letter, so it requires a deep understanding to know the difference. The disclosure of the meaning of Manna and Salwa> will be the author of the analysis using semantics, and the interpretation of the Qur'an and its Exegesis and al-Mishbah tafsir. The process carried out in this study is: the author will present the data in the form of verses of the Qur'an related to lafazd Manna and Salwa> and clarify it. Then the author will analyze using semantic theory with the following stages : The first step is to search for keywords, then find the basic meaning and relational meaning, then look for synchronized concepts with. Tracing the definitions of Manna and Salwa> with pre-Qur'anic, Post-Qur'anic, Post-Qur'anic, then presents the Weltanschauung of the word. After studying using semantic theory, the author will conduct a critical study, namely analyzing the meaning of the words Manna and Salwa> in the Tafsir of the Qur'an and its Tafsir, and Tafsir Al-Mishbah.